2011
DOI: 10.1074/jbc.m110.153965
|View full text |Cite
|
Sign up to set email alerts
|

Location of Glycine Mutations within a Bacterial Collagen Protein Affects Degree of Disruption of Triple-helix Folding and Conformation

Abstract: The hereditary bone disorder osteogenesis imperfecta is often caused by missense mutations in type I collagen that change one Gly residue to a larger residue and that break the typical (Gly-Xaa-Yaa) n sequence pattern. Site-directed mutagenesis in a recombinant bacterial collagen system was used to explore the effects of the Gly mutation position and of the identity of the residue replacing Gly in a homogeneous collagen molecular population. Homotrimeric bacterial collagen proteins with a Gly-to-Arg or Gly-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…However, the glycine substitution G1519D located in another segment of the triple helix had no effect on procollagen VII secretion or its ability to anchor fibril assembly. These data showed that the biological impact of glycine substitutions can depend on their position within the triple helix, as shown for collagen I (Cheng et al, 2011).…”
Section: Lessons From Site-directed Mutagenesis Of Recombinant Collagsupporting
confidence: 54%
See 1 more Smart Citation
“…However, the glycine substitution G1519D located in another segment of the triple helix had no effect on procollagen VII secretion or its ability to anchor fibril assembly. These data showed that the biological impact of glycine substitutions can depend on their position within the triple helix, as shown for collagen I (Cheng et al, 2011).…”
Section: Lessons From Site-directed Mutagenesis Of Recombinant Collagsupporting
confidence: 54%
“…A very recent study utilized a recombinant bacterial collagen to develop a mutagenesis scheme in which a glycine residue within the triple-helix sequence is substituted with arginine or serine. The purpose was to analyze the positional effect of glycine mutations on triple-helix formation and stability (Cheng et al, 2011). Interestingly, all glycine mutations provoked a significant delay in the triple-helix formation.…”
Section: Lessons From Site-directed Mutagenesis Of Recombinant Collagmentioning
confidence: 99%
“…The measured CD spectrum of MAC resulted in similar spectra to that of native collagen spectra with an Rpn value of 0.13 indicating the retention of the triple helical assembly after >85% modification of collagen's lysines. 32,33 Sameness in Rpn values after methacrylate modification indicates the specific functionalization of collagen at ε amines of lysine that did not alter the triple helical propensity. From our CD spectroscopic analysis it is evident that the intrinsic structure of collagen was largely retained after modification (Fig.…”
Section: Structural Elucidation Of Methacrylated Collagen (Mac)mentioning
confidence: 99%
“…The recombinant bacterial collagen system has been applied to characterize the effects of a Gly mutation, since a mutation can be introduced at any location within the triple-helix while controlling the sequence surrounding it (Cheng et al 2011). Site-directed mutagenesis was used to introduce a Gly→Arg or a Gly→Ser mutation at a site near the middle or near the N-terminus of the triple-helix adjacent to the trimerization domain.…”
Section: Manipulation Of Triple-helix In Recombinant Bacterial Colmentioning
confidence: 99%